PENGARUH KONSENTRASI KOLKISIN DAN APLIKASI TANDAN KOSONG KELAPA SAWIT TERHADAP PRODUKSI KEDELAI (Glycine max L.) CEKAMAN KEKERINGAN - Buulolo, Faano; Saragih, Wismaroh Sanniwati; Sibagariang, Edison (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Soybean (Glycine max L.) production can be increased through the introduction of colchicine mutation induction to obtain plants that are resistant to disease, and the use of oil palm empty fruit bunches (TKKS) to overcome drought stress can increase soybean production. The aim of the research was to determine the effect of colchicine and the use of TKKS organic materials on increasing soybean production. The research was carried out from June to September 2023 on the agro-agricultural land of the Universitas Pembinaan Masyarakat Indonesia, Jl. Marindal II Village Hall, Pasar 12, Medan. The experiment used a factorial randomized block design (RAK) with colchicine (K) concentration treatment (0; 0.01%; and 0.05%) and EFB organic matter interval (M) (0; 5 kg/plot 1 WAP; and 10 kg/plot 5 WAP) repeated three times for each treatment. The results showed that soybeans treated with colchicine concentration had a very significant effect on plant height, flowering age, number of pods per sample, and seed weight per sample per plot at a concentration of 0.05% with a soaking time of 15 hours. The application of EFB organic material had a very significant effect on plant height, flowering age, number of sampled pods, and sampled seed weight at a dose of 10 kg/plot. The combination of treatments, namely K2T3 (0.05% + 10 kg/plot), is thought to have the response of both treatments simultaneously supporting the growth and production of soybean plants.